"I Don't Get It. I Need Help": Emergent Bilinguals Seeking and Receiving Help From Peers in Language Arts. Issue 2 (3rd April 2019) - Rodriguez-Mojica, Claudia
ABSTRACT: This study examines how emergent bilinguals seek help in language arts and how peers respond to their requests for help. Using 6 months of naturally occurring student talk in a U.S. fourth grade classroom, this article shows that (a) emergent bilinguals more frequently use general requests than specific requests to obtain help, (b) only 41% of emergent bilingual requests for help succeeded in eliciting helpful peer responses, and (c) there is no significant difference between specific and general requests for help and help received. Findings suggest the need for policies and practices that foster the educational environments necessary for peer collaboration that promotes academic understanding.